2009
DOI: 10.3109/13814780903452184
|View full text |Cite
|
Sign up to set email alerts
|

The Research Agenda for General Practice/Family Medicine and Primary Health Care in Europe. Part 1. Background and methodology1

Abstract: At the WONCA Europe conference 2009 the recently published 'Research Agenda for General Practice/Family Medicine and Primary Health Care in Europe' was presented. The Research Agenda is a background paper and reference manual for GPs/ family doctors, researchers and policy makers, providing advocacy of general practice/family medicine GP/FM in Europe. The Research Agenda summarizes the evidence relating to the core competencies and characteristics of the WONCA Europe definition of GP/FM, and its meaning for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 35 publications
0
49
0
17
Order By: Relevance
“…In the WONCA tree, the roots of family medicine are fed from science. 23 Family physicians should be a pioneer in the field of informatics and benefiting from science. thesis and scientific research should be perceived as a chance, not as an obligation in the family medicine residency training course.…”
Section: Discussionmentioning
confidence: 99%
“…In the WONCA tree, the roots of family medicine are fed from science. 23 Family physicians should be a pioneer in the field of informatics and benefiting from science. thesis and scientific research should be perceived as a chance, not as an obligation in the family medicine residency training course.…”
Section: Discussionmentioning
confidence: 99%
“…5 It also reflects, in the specific context of respiratory disease, the broad themes of generic primary care research priorities, including organisation of accessible, community-based, integrated care, clinical problem solving (encompassing diagnosis, treatment and management), and a comprehensive, holistic, patient-centred costeffective approach. 1 A core message of all primary care research agendas (clearly echoed in this document) is the need for research undertaken within primary care, recruiting patients representative of primary care populations, evaluating interventions realistically delivered within primary care, and drawing conclusions that will be meaningful to professionals working within primary care.…”
Section: The Role Of the Ipcrg Research Needs Statementmentioning
confidence: 99%
“…1 Respiratory disease exemplifies all these agendas. In many countries, respiratory symptoms are the commonest reason for presentation to primary care, encompassing both acute infections (pneumonia and the familiar if ill-defined 'chest infections') and long-term conditions such as asthma, rhinitis, and chronic obstructive pulmonary disease (COPD).…”
Section: The Importance Of Primary Care Respiratory Researchmentioning
confidence: 99%
“…At its centre is the patient, as a complete biopsychosocial being, approached holistically and provided with continuing care over time, with the focus on the family and community. The framework for research topics is shown in the detailed document: "Research Agenda for General Practice / Family Medicine and Primary Health Care in Europe, " in the form of a manual for GP-researchers in family medicine and health policymakers, written by a group of experts from the organization, the European General Practice Research Network (EGPRN), of the World Organization of National Colleges, Academies and Academic Associations of General Practitioners/Family Physicians (WONCA) for Europe (8). The Agenda complements the European Academy of Teachers in General Practice/Family Medicine (EURACT) Educational Teaching Agenda, which addresses academic and vocational training (9).…”
Section: The Tradition Of Research In the Family Medicine Settingmentioning
confidence: 99%